Implikasi Filsafat Ilmu dalam Optimalisasi penanganan kredit macet melalui akad murabahah di PT BSI KCP Cemara asri - Anisah Cyntia Dewi Pratama; Budi Harianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the implications of the philosophy of science in optimizing the management of non-performing loans through murabahah contracts at PT BSI KCP Cemara Asri. It aims to analyze how the philosophy of science can deepen the understanding of non-performing loan phenomena, identify the causes from the philosophy of science perspective, and formulate effective management strategies. A qualitative method with a case study approach was employed, involving in-depth interviews and participatory observation. Findings suggest that a balanced qualitative and quantitative understanding and the strong application of Sharia principles can reduce the risk of non-performing loans. The practical and theoretical implications of this study are expected to contribute to the improvement of overall Islamic banking practices.